ANALISIS RASIO PROFITABILITAS SEBAGAI ALAT UKUR UNTUK MENILAI KINERJA KEUANGAN PT. UNITED TRACTORS Tbk DI BURSA EFEK INDONESIA - Murnawati, Murnawati; Erti, Lili; Tasril, Tasril (Jurnal Daya Saing, 2024)
The increasingly rapid development of the business world in Indonesia has made this country a destination for local and foreign investors, changes in the business environment are also quite an attractive factor for investors, PT United Tractors Tbk is a construction business unit, and carries out its role as a leading heavy equipment distributor and largest in Indonesia, the aim of the research is to determine the profitability ratio, the profitability ratio is to determine the company's ability to generate profits in a certain period. The policy carried out is to assess the profitability ratio which consists of Gross Profit Margin (GPM) Net Profit Margin (NPM) and Return On Assets (ROA), Return On Equity (ROE). from 2018-2023 This research uses a descriptive method using secondary data. The results of the research are seen from the Profitability ratios, Gross Profit Margin, Net Profit Margin, Return On Assets, with the results in the good category, because they are above industry standards, while for the Return On ratio Equity calculation results in the category are not good because they are below industry standards, Keywords: Profitability,GPM, NPM, ROA, ROE Financial Performance